Family Resilience Scale Short Form (FRS16): Validation in the US and Chinese Samples - Chow, Tak Sang; Tang, Catherine So Kum; Siu, Tiffany Sok U.; Kwok, Helen Sin Hang (Frontiers in Psychiatry, 2022)
Family resilience, which refers to the processes through which a family adapts to and thrives from adversities, has growing importance in recent years. In response to the need for further research on family resilience, the present research aims to abbreviate and validate Sixbey's Family Resilience Assessment Scale (FRAS) into a 16-item version Family Resilience Scale Short Form in the US (FRS16) and Chinese (FRS16_C) samples. The samples included 1236 (Study 1) and 1135 (Study 2) participants from the US and China respectively. Results of confirmatory factor analysis (CFA) supported the proposed three-factor structure of FRS16: Family Communication and Connectedness, Positive Framing, and External Support across two samples. Overall, the reliability and validity of full and subscales of FRS16 and FRS16_C were satisfactory. Multi-group CFA revealed that both configural and metric invariance are supported, suggesting that participants in the US and Chinese samples assign comparable meaning to the latent factors of FRS16. Results suggested that FRS16 and FRS16_C are valid instruments for family resilience in the US and Chinese samples.